并联机构工作空间与奇异位形分析 - 史革盟; 鲁开讲 (Jixie chuandong)
The relationship of workspace and structure parameter of three degree of freedom planar parallel mechanism is established by using the geometric analysis method,the changes of the shape of working space with the structure parameters is studied,and the condition for the mechanism meet the possibility of the movement is proposed.Taking the requirements of the mechanism on the workspace as geometric constraints to the structure parameters,and the optimization design is carried out to meet the requirements of working space,as well as the other performance requirement of mechanism.The relationship between position and velocity of the mechanism is built on the basis of the inverse kinematics,taking the mechanism satisfying geometric constraints as the criterion,the entire configuration space of mechanism is explored,the reason of mechanism generating singularity from the perspective of geometry is analyzed,the singular configuration distribution in the working space and the space segmentation is researched and the method for determining the mechanism without singularity workspace is presented.